Correlation between initial serum levels of lactate after return of spontaneous circulation and survival and neurological outcomes in patients who undergo therapeutic hypothermia after cardiac arrest. (March 2015) - Lee, Dong Hoon; Cho, In Soo; Lee, Sun Hwa; Min, Yong Il; Min, Jin Hong; Kim, Soo Hyun; Lee, Young Hwan; ,
Abstract: Objectives: We analysed the relationship between serum levels of lactate within 1 h of return of spontaneous circulation (ROSC) and survival and neurological outcomes in patients who underwent therapeutic hypothermia (TH). Methods: This was a multi-centre retrospective and observational study that examined data from the first Korean Hypothermia Network (KORHN) registry from 2007 to 2012. The inclusion criteria were out-of-hospital cardiac arrest (OHCA) and examination of serum levels of lactate within 1 h after ROSC, taken from KORHN registry data. The primary endpoint was survival outcome at hospital discharge, and the secondary endpoint was poor neurological outcome (Cerebral Performance Category, CPC, 3–5) at hospital discharge. Initial lactate levels and other variables collected within 1 h of ROSC were analysed via multivariable logistic regression. Results: Data from 930 cardiac arrest patients who underwent TH were collected from the KORHN registry. In a total of 443 patients, serum levels of lactate were examined within 1 h of ROSC. In-hospital mortality was 289/443 (65.24%), and 347/443 (78.33%) of the patients had CPCs of 3–5 upon hospital discharge. The odds ratios of lactate levels for CPC and in-hospital mortality were 1.072 (95% confidence interval (CI) 1.026–1.121) and 1.087 (95% CI = 1.031–1.147), respectively, based on multivariate ordinal logistic regression analyses. Conclusion: High levels of lactate in serum measured within 1 h of ROSC are associated with hospital mortality and high CPC scores in cardiac arrest patients treated with TH.